2010
DOI: 10.1039/b917184n
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity of rare earth and transition metal thiophosphates

Abstract: Technological interest in the design of solid state materials has stimulated recent research into the development of mild molten polychalcophosphate salt fluxes for the synthesis of complex, multinary rare earth and transition metal thiophosphate compounds. The reaction pathways from elemental or metal sulfide sources can be influenced by a variety of often interdependent factors of which counter cation sizes and charges, basicity, and temperature are of paramount importance. In rare earth and transition metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 107 publications
1
50
0
Order By: Relevance
“…The As-S bond lengths of 2.248(3), 2.264(2), and 2.286(2)Å belong to the "non-bridge" category described by Takeuchi et al [46]. The S-As-S bond angles of 96.97(9), 97.35 (10), and 102.60(10) • (mean: 98.97 • ) correspond very well to those in KSnAsS 5 [31]. The next nearest S neighbors are located at a distance longer than 3.35Å which is too far apart for As-S bonding interactions.…”
Section: Crystal Structuresmentioning
confidence: 97%
See 2 more Smart Citations
“…The As-S bond lengths of 2.248(3), 2.264(2), and 2.286(2)Å belong to the "non-bridge" category described by Takeuchi et al [46]. The S-As-S bond angles of 96.97(9), 97.35 (10), and 102.60(10) • (mean: 98.97 • ) correspond very well to those in KSnAsS 5 [31]. The next nearest S neighbors are located at a distance longer than 3.35Å which is too far apart for As-S bonding interactions.…”
Section: Crystal Structuresmentioning
confidence: 97%
“…Group 15 chalcogenides are very interesting not only because of their potential application as thermoelectric materials, such as Sb 2 Te 3 [1], AgPb 18 SbTe 20 [2], Mo 3 Sb 5 Te 2 [3], and AgSb x Bi 3−x S 5 [4], and nonlinear optical materials, such as AAsQ 2 (A = Li, Na; Q = S, Se) [5,6], A 3 Ta 2 AsS 11 (A = K, Rb) [7], AZrPQ 6 (A = K, Rb, Cs; Q = S, Se) [8,9], but also because of their structural diversity [10], which arises partly from the various local coordination environments centered by group 15 elements. Unlike its heavier homologues Sb and Bi, trivalent arsenic exhibits a remarkable reluctance to adopt hypervalent coordination polyhedra in its chalcogenido anions [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the applied excess of the other elements, TiS 2 and ternary Ti-thiophosphates are found as by-products, and also Cu 3 PS 4 was observed. Interestingly, an analogous synthesis route using sulfides as starting materials (A 2 S, TiS 2 , and P 4 S 10 ) also leads to ATi 2 (PS 4 ) 3 (A = Li, Na and Ag), whereas the copper sulfide-containing mixtures neither yield CuTi 2 (PS 4 ) 3 -units or parts of them. In previous studies Kanatzidis et al have shown that elemental Cu has been oxidized in the presence as well as in the absence of elemental S during the reactions in molten mixtures of alkali metal sulfides and P 4 S 10 .…”
Section: Short Communicationmentioning
confidence: 99%
“…Within the group of titanium thiophosphates, besides two ternary compounds [1,2] only a few quaternary compounds have been structurally characterized. [3] As a prominent feature, their structures are built from TiS 6 octahedra and PS 4 tetrahedra, which are connected via common edges, and in which each S atom often coordinates two cations. The connection pattern is mainly determined by the Ti/P ratio, with larger Ti contents leading to interconnected TiS 6 octahedra, whereas P-rich compounds contain different thiophosphate anions like (P 2 S 6 ) 2-, [2] the corner-sharing units (P 2 S 7 )…”
Section: Introductionmentioning
confidence: 99%